The Litchfield pluton in south-central Maine: Carboniferous alkalic magmatism in northern New England, USA - West, David; Bradley, Dwight; Coish, Raymond (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2016)
ABSTRACT The Litchfield pluton is a poorly exposed 7 km2 composite alkalic intrusive complex that cuts previously deformed and metamorphosed Silurian turbidites in south-central Maine. The pluton includes a variety of alkaline syenites, including the type locality of “litchfieldite,” a coarse-grained cancrinite-, sodalite-, and lepidomelane-bearing nepheline syenite first recognized over 150 years ago and common in many petrologic collections. A new U-Pb zircon age of 321 ± 2 Ma from the nepheline syenite is interpreted to represent the crystallization age of the plutonic complex. A new biotite 40Ar/39Ar age of 239 ± 1 Ma from the syenite is similar to previously published mica ages from the surrounding country rocks and dates the time of regional cooling in the area below ~ 300°C. Whole-rock chemical analyses of rocks of the Litchfield pluton reveal silica-undersaturated alkaline compositions that are consistent with formation in a within-plate tectonic setting. The age and geochemical characteristics of the alkalic igneous rocks near Litchfield are consistent with a model that invokes the generation of a small volume of alkalic magma beneath south-central Maine during a period of Carboniferous transcurrent tectonism in the northern Appalachian orogen.